2020
DOI: 10.1101/2020.05.02.20088427
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19 Pandemic Prediction for Hungary; a Hybrid Machine Learning Approach

Abstract: Several epidemiological models are being used around the world to project the number of infected individuals and the mortality rates of the COVID-19 outbreak. Advancing accurate prediction models is of utmost importance to take proper actions. Due to a high level of uncertainty or even lack of essential data, the standard epidemiological models have been challenged regarding the delivery of higher accuracy for long-term prediction. As an alternative to the susceptibleinfected-resistant (SIR)-based models, this… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
59
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(60 citation statements)
references
References 93 publications
0
59
0
1
Order By: Relevance
“…Pinter et al use hybrid machine learning methods of adaptive network-based fuzzy inference system (ANFIS) and multi-layered perceptron-imperialist competitive algorithm (MLP-ICA) to predict time series of COVID-19 infected individuals and mortality rate (Pinter et al. 2020 ). Erraissi et al present a Spark ML approach to predict COVID-19 cases (Erraissi et al.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Pinter et al use hybrid machine learning methods of adaptive network-based fuzzy inference system (ANFIS) and multi-layered perceptron-imperialist competitive algorithm (MLP-ICA) to predict time series of COVID-19 infected individuals and mortality rate (Pinter et al. 2020 ). Erraissi et al present a Spark ML approach to predict COVID-19 cases (Erraissi et al.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Pinter et al [ 17 ] proposed a hybrid machine learning method to predict COVID-19 cases in Hungary. Adaptive neuro-fuzzy inference system (ANFIS) has been combined with multilayered perceptron-imperialist competitive algorithm (MLP-ICA) to anticipate the time series of infected persons and mortality rate.…”
Section: Related Workmentioning
confidence: 99%
“…Other applications of ANFIS for disease forecasts include: Hepatitis C virus epidemic ( Khodaei-mehr, Tangestanizadeh, Vatankhah, & Sharifi, 2018 ), tuberculosis ( Mohammed et al, 2018 , Uçar et al, 2013 ), and finally, COVID-19. The COVID-19 related applications include forecasting the confirmed cases of the COVID-19 in China ( Al-qaness, Ewees, Fan, & Aziz, 2020 ), outbreak prediction ( Ardabili et al, 2020 ) and prediction case-study on the state of Hungary ( Pinter et al, 2020 ). Since the COVID-19 is a relatively new challenge, only a few studies have been found from this domain.…”
Section: Background and Related Workmentioning
confidence: 99%
“…The conclusion of this research suggests that machine learning can be used effectively to model the outbreak of the disease. This approach was later exemplified on the case of Hungary ( Pinter, Felde, Mosavi, Ghamisi, & Gloaguen, 2020 ), in order to demonstrate the potential of the machine learning approach and to set a path for future research. The research presented in Suzuki and Suzuki (2020) utilize machine learning approach to estimate the number of reported cases in each province of South Korea, by employing a combination of XGBoost and MultiOutputRegressor as a machine learning model.…”
Section: Introductionmentioning
confidence: 99%